Strategi Fundraising dalam Mengoptimalkan Jumlah Penerimaan Zakat pada LAZ Harapan Dhuafa di Kota Serang - Fathurrohman, Muhammad Khaeru; Karim, Muhammad Luthfan; Najib, Mohamad Ainun (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2025)
This research aims to find out the zakat fundraising strategy in optimizing the amount of zakat revenue at LAZ Harapan Dhuafa in Serang City, Banten Province. Descriptive qualitative is the type of this research. Observation, interview, and documentation are part of the data collection methods of this research. Data analysis techniques that can support this research, namely data reduction, data presentation, and conclusion or verification. The findings of this study, LAZ Harapan Dhuafa in implementing fundraising strategies are divided into two, namely direct and indirect. The direct fundraising strategy implemented by LAZ Harapan Dhuafa, namely retail fundraising, pick up zakat, marketing campaigns. While the indirect fundraising strategy implemented by LAZ Harapan Dhuafa, namely promotional activities on social media, websites, and bank transfers or E-Wallets and through the Kitabisa application. In addition, the supporting and inhibiting factors have been identified by researchers. It is necessary for LAZ administrators to continuously socialize and develop effective and efficient zakat fundraising strategies that support the development of the 5.0 revolution era, especially in promotional activities.